Junctional ER Organization Affects Mechanotransduction at Cadherin-Mediated Adhesions - Joy-Immediato, Michelle; Ramirez, Manuel J.; Cerda, Mauricio; Toyama, Yusuke; Ravasio, Andrea; Kanchanawong, Pakorn; Bertocchi, Cristina (Frontiers in Cell and Developmental Biology, 2021)
Cadherin mediated adhesions are adhesive complexes that connect neighboring cells in a tissue. While the role of the actin cytoskeleton in withstanding tension at these sites of contact is well documented, little is known about the involvement of the microtubule and the associated endoplasmic reticulum (ER) network in cadherin mechanotransduction. Therefore, we investigated how the organization of ER extensions in close proximity of cadherin-mediated adhesions can affect such complexes, and vice versa. Here we show that the extension of the ER to cadherin-mediated adhesions is tension dependent and appears to be cadherin type specific. Furthermore, the different structural organization of the ER/microtubules network seems to affect the localization of ER-bound PTP1B at cadherin-mediated adhesions. This phosphatase is involved in the modulation of vinculin, a molecular clutch which enables differential engagement of the cadherin-catenin layer with the actomyosin cytoskeleton in response to tension. This suggests a link between structural organization of the ER/microtubules network around cadherin-specific adhesions, to control the mechanotransduction of AJs by modulation of vinculin conformational state.